A Review of Six Sigma and the Shared Relationship with Knowledge Management (KM) Discipline - Chukwuebuka Martinjoe U-Dominic; Harold Chukwuemeka Godwin (Archives of Current Research International, 2018)
Six Sigma and KM are two distinct disciplines that support each other, and subsequently, create a strong foundation for learning when used concurrently in an organizational context. Although, six sigma objectives tend towards process improvement while KM objective is all about the right flow of information and knowledge, however, there is a very powerful intersection and synergy between the two disciplines that promote process performance. The reported cases on failed six sigma projects have been on the rise, due to organization's inability to create a learning environment, fit enough to engage employee's capabilities in solving quality related problems such that knowledge of the process is retained and not lost after the six sigma project. Recently, very few organizations are now acquainting themselves with these two notable improvement strategies in quest of becoming more ambidextrous to positively frame process problem as an opportunity for improvement. This paper explored the potentials of these two disciplines, by taking a narrative review both from the academic and in the practitioner's point of view to bring to limelight their level of synergy and appreciation both in scholarly and in organizational domain. This study has underscored the level of awareness and poor utilization of these two disciplines in improving organizational performance among manufacturing firms. The paper further expounds on the need for organizations to focus in building an organic knowledge structure that will favourably sustain newly-stabilized processes, and also suggest for more integration of both disciplines since there is no standardized model(s) of integration of six sigma-DMAIC and KM to widely capture knowledge on other integration tactics.